2021
DOI: 10.3389/feart.2021.697728
|View full text |Cite
|
Sign up to set email alerts
|

Particulate and Dissolved Black Carbon in Bohai and Laizhou Bays, China: Distributions, Sources, and Contrasts Under Two Distinct Fluvial Hydrological Regimes

Abstract: Coastal seas, including coastal bays, are the geographically critical transitional zone that links terrestrial and open oceanic ecosystems. Organic carbon cycling in this area is a dynamic and disproportionally key component in the global carbon cycle and budget. As the thermally-transformed organic carbon produced exclusively from the incomplete combustion of biomass and fossil fuels, the recalcitrance and resultant longer environmental residence times result in important implications of black carbon (BC) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 78 publications
(154 reference statements)
4
15
1
Order By: Relevance
“…Our findings, however, are in good agreement with recent studies, indicating that DBC has much higher Δ 14 C values (50 to −200‰) and modern to younger 14 C ages in the Yangtze, Yellow, and Heilongjiang Rivers in China , and in the Amazon River . Our study, together with other studies, demonstrates that a large amount of BC produced from biomass burning on the land can be transformed into the dissolved phase and then mobilized and transported by streams and rivers to coastal seas. ,,,, Similarly, after PBC deposition, the biomass-derived can be further transferred to porewater DBC during early diagenesis. Thus, the fate and transformation of DBC are important processes in BC cycling.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings, however, are in good agreement with recent studies, indicating that DBC has much higher Δ 14 C values (50 to −200‰) and modern to younger 14 C ages in the Yangtze, Yellow, and Heilongjiang Rivers in China , and in the Amazon River . Our study, together with other studies, demonstrates that a large amount of BC produced from biomass burning on the land can be transformed into the dissolved phase and then mobilized and transported by streams and rivers to coastal seas. ,,,, Similarly, after PBC deposition, the biomass-derived can be further transferred to porewater DBC during early diagenesis. Thus, the fate and transformation of DBC are important processes in BC cycling.…”
Section: Discussionsupporting
confidence: 92%
“…The Yangtze and Yellow Rivers are the two largest rivers in China, and their estuaries and adjacent shelf regions are highly dynamic due to large inputs of freshwater and terrestrial materials. The Yangtze and Yellow Rivers together deliver over 90% of the fresh water to the East China Sea and Bohai Sea. , Recent studies have shown that large amounts of BC are transported by the two rivers into coastal regions. ,, Our previous studies have demonstrated that the Yangtze River exports ∼192 Gg (1 Gg = 10 9 g) of particulate BC (PBC) to the East China Sea annually, and the Yellow River delivers ∼12 Gg of PBC to the Bohai Sea annually. , In addition, atmospheric deposition could contribute 55 ± 19 Gg aerosol PBC to the East China Sea and ∼88 Gg aerosol PBC to the Bohai Sea annually. , Large amounts of this river- and atmospherically transported PBC are deposited and buried in the sediments of the estuaries, making the two estuaries ideal regions for studying the transformation and cycling of BC in sediments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations